ANALYSIS OF MOTORCYCLE TRAFFIC ACCIDENT BASED ON THE RIDERS’ CHARACTERISTICS IN KUPANG, EAST NUSA TENGGARA - Hera Widyastuti; Leila Adriana (Journal of Civil Engineering, 2022)
Awareness about driving safety is still lacking among motorcycle users. As the provincial capital of East Nusa Tenggara (NTT), Kupang city accounts for the largest number of accidents in NTT with 70% of the total accidents involving motorcycles. It is important to measure the extent to which riding characteristics affects and causes road accidents since humans as the riders are the main factor in traffic accidents. A questionnaire was distributed to the motorcyclists. The data collected from 212 respondents was analysed with the multivariate logistic regression method. The analysis result states that the motorcycle mileage and the motorbike ownership hold the most influence on the incidence of motorcycle road accidents, where the further the motorcycle riders travel, the higher the probability of them to get involved in a road accident. Meanwhile the more units of motorcycle owned, the lower the probability of them to get involved in a road accident.